Leadership Style and Employee Readiness: the Main Factors of Leadership Efficiency - Rodić, Marijana; Marić, Slobodan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The scope of this study is based on the Situational leadership theory according to the model created by Hersey and Blanchard, predominantly defined by two research sub-fields: leadership style and readiness of employees. This model distinguishes four different leadership styles, while the subject area of readiness of employees comprises two components: readiness of employees based on a competency component and readiness of employees based on a psychological (motivational) component. The subject matter of the study is to identify leadership efficiency as a new variable which will be utilized for determining the correlation between leadership efficiency levels and readiness of employees. Leadership efficiency is determined by the degree of compatibility between the dominant style of leadership and the level of readiness of employees. In addition to the main objective of the research, aimed at determining leadership efficiency, significant research findings come as a result of specific objectives such as the impact of the dominant leadership style on readiness of employees both on the whole and on the basis of each specific component. The sample will be a random sample from a finite population of units, with repeated sampling and known probability sampling. A sample of size n=100, that has a proportion of 0.10, is based on a list of top 100 biggest companies in the Republic of Serbia in 2019. The application of Principal Component Analysis aims at identifying new variables in the form of regression coefficient results, while the application of the hierarchical regression model will help determine the impact of each leadership style on readiness of employees. The study findings confirm the basic hypotheses of the aforementioned model, with regard to the results of leadership efficiency, as well as its impact of each leadership style on readiness of employees.